REGISTRATION SERVICE FOR THE CERTIFICATE OF REGISTRATION (SKT) FOR NON-LEGAL ENTITY MASS ORGANIZATIONS AT THE NATIONAL UNITY AND POLITICS AGENCY (BANKESBANGPOL) OF HULU SUNGAI UTARA REGENCY - Riza Hendriani; Sugianor Sugianor; Djayeng Turano Gunade (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
This study aims to determine the factors that influence the registration service for Registered Certificate (SKT) for non-legally incorporated mass organizations at the National Unity and Politics Agency (BANKESBANGPOL) of Hulu Sungai Utara Regency. The study uses a qualitative approach with a descriptive-qualitative type. By collecting data in the form of data and sentences through observation, interviews, and documents. Data sources are taken through purposive sampling of informants. Credibility testing with extended observation, increased persistence, triangulation, negative case analysis and member check. Registration Service for the Certificate of Registration (SKT) for Non-Legal Entity Mass Organizations at the National Unity and Politics Agency (Bankesbangpol) of Hulu Sungai Utara Regency is not good as seen from the following variables and indicators: First, Transparency, Openness of service is not good. Service procedures are not good yet. Ease of information is not good yet. Second, Accountability, Public service performance is not good yet. Service costs are good. Service products are not good yet. Third, Conditional, efficient is not good yet. Effective is not good yet. Fourth, Participatory, community role is quite good. Community expectations are not good yet. Fifth, equality of rights and assertiveness are good. Non-discrimination is good. Sixth, balance of rights and obligations, Supporting factors are No fees for services, Firmness of officers in services, Fair and equal service/non-discrimination. Inhibiting factors include budget limitations, an insufficient number of employees skilled in managing mass organizations, and the suboptimal timeframe for completing the SKT (Credit Card) (SKT).